Legal Measure Relating to Consumer Protection for Advertisements in CLMVT Countries - Shookpreedah, Aukkarachaiwuth; Saowakon, Siwaporn (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Trade between the CLMVT groups brings with it the consumers of each country, causing both traders or entrepreneurs and consumers to occur. The problem is that being a consumer in this CLMVT group has the same status as being a consumer. However, the problem is how to provide consumers in each country with the same protection. Thus, this paper aims to (1) investigate the background, principles, and theories related to consumer protection for advertisements in CLMVT countries, (2) explore legal measures of Thailand and foreign countries on consumer protection for advertisements in CLMVT countries, (3) analyze the problems and obstacles on consumer protection for advertisements in CLMVT countries, and (4) propose approaches to solve the problems on consumer protection for advertisements in CLMVT countries. Methodology: This thesis is qualitative research using documentary research methods. This thesis studies the legal measures relating to consumer protection for advertisements in CLMVT countries. Results: The findings were as follows: (1) Regarding the problems of advertisement definition, the CLMVT countries specify their definition of “advertisement”; (2) Regarding the legal problems of the rights of advertisement, the CLMVT countries stipulate the rights of advertisement to be appropriate for their people; (3) Regarding the problems of the advertising committees, the CLMVT countries do not issue the provisions on the Central Advertising Committees; and (4) Regarding the problem of roles and duties of the advertising committees, the CLMVT countries do not legislate the roles and duties of the Central Advertising Committees leading consumer protection for advertisements in CLMVT countries to be appropriate to be enforced with their people, as well as the lack of the central standard and equality among the CLMVT countries. Therefore, the researcher would like to propose the central law on consumer protection for advertisements in CLMVT countries as follows: (1) the definition of “advertisement,” (2) the rights of advertisement, (3) the advertising committees, and (4) duties and roles of the advertising committees. Conclusion: The study identifies significant challenges in advertising regulation within the CLMVT group, including divergent definitions, varied legal rights, the absence of a central regulatory body, and undefined roles for regulatory committees. To address these issues and ensure consumer protection, the researcher recommends the implementation of standardized laws covering the definition of advertising, advertising rights, and the establishment and functions of regulatory committees within the CLMVT region.